THE IMPACT OF FINANCIAL SUSTAINABILITY ON THE PERFORMANCE OF THE IRAQI BANKING SECTOR: AN APPLIED STUDY ON PRIVATE COMMERCIAL BANKS IN BAGHDAD (World Economics and Finance Bulletin, 2025)
This research aims to investigate the impact of financial sustainability on the performance of the banking sector in Iraq across three main aspects: profitability, operational efficiency, and asset growth. Meanwhile, financial sustainability will be studied through three primary dimensions: financial resource management efficiency, diversification of funding sources, and financial stability. Based on the study's objectives, a sampling method was chosen to test the hypotheses, where the study sample was identified as three banks: Al-Mansour Bank, the Iraqi Islamic Commercial Bank, and Baghdad Bank. The population size in these banks was 300 employees, and the research sample was determined as 150 employees through Simpson's formula, representing 50% of the basic population size. The researcher relied on a questionnaire to collect the basic research information, distributing 179 questionnaires. A total of 163 questionnaires were retrieved at a response rate of 91%, while 13 questionnaires were rejected due to their ineligibility for statistical analysis because they were incomplete or contained errors, accounting for 7.2% of the original sample size. We obtained the required number of 150 questionnaires with a response rate of 83.7%. The data were analyzed using the SPSS 25 statistical software. A variety of statistical methods were employed, including calculating the mean, correlation coefficients, and simple regression analysis, along with utilizing a five-point Likert scale for individual responses within the sample. The researcher concluded with several findings, the most significant being that financial sustainability strongly affects the performance of the banking sector in Iraq across its various dimensions. The researcher recommended that private commercial banks in Iraq should strive to diversify their revenue and investment sources to ensure long-term financial sustainability.
Keywords: Financial Sustainability; Banking Sector Performance; Profitability